PENGELOLAAN PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI, DAN SOSIOLOGI - Istanto; Mulyono; Muhammad Al Mighwar; Ujang Nurjaman (al-Afkar, Journal For Islamic Studies, 2022)
This study aims to describe and analyze what, why, and how of education management based on religion, philosophy, psychology, and sociology. From this research, it was concluded that education management is planning, implementing, and supervising educational resources which are: (1) based on religion means based on God's teachings that command comprehensive arrangements, by means of proper and accurate planning, implementation, and supervision; (2) based on philosophy means based on a realistic study of nature and the meaning of life, by thinking rationally, naturally scientifically, harmoniously, and critically; (3) based on psychology means based on a comprehensive scientific study of the human mind and behavior, by means of introspection, experimentation, and comparison; and (4) based on sociology means based on social scientific studies that require progress, with a progressive, rational, and conscious society perspective.